1996
DOI: 10.12693/aphyspola.90.763
|View full text |Cite
|
Sign up to set email alerts
|

On GaN Crystallization by Ammonothermal Method

Abstract: GaN crystals are grown using ammonothermal method at pressures below 5 kbar and temperatures below 550°C. In this method, GaN is synthesised from high purity metallic gallium. The main role in the low temperature GaN crystallization is played by the chemically active and dense ammonia and dissolved mineralizer. Morphology of the obtained crystals as well as solubility experiments prove that gallium nitride is dissolved and crystallised from solution. Physical properties of GaN crystals obtained using ammonothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 2 publications
1
53
0
Order By: Relevance
“…In the mid-1990s Dwiliński et al had first demonstrated that it is possible to get crystalline GaN by a chemical reaction between gallium and ammonia, in the presence of alkali metal amides (LiNH 2 or KNH 2 ) as mineralizers [49,50]. GaN was synthesized using supercritical ammonia and metallic gallium, at the temperature of 500…”
Section: Ammonothermal Methodsmentioning
confidence: 99%
“…In the mid-1990s Dwiliński et al had first demonstrated that it is possible to get crystalline GaN by a chemical reaction between gallium and ammonia, in the presence of alkali metal amides (LiNH 2 or KNH 2 ) as mineralizers [49,50]. GaN was synthesized using supercritical ammonia and metallic gallium, at the temperature of 500…”
Section: Ammonothermal Methodsmentioning
confidence: 99%
“…It is also known that various bulk binary nitrides are formed from the metal in supercritical ammonia using an ammonobasic mineralizer (see paragraph Nitrides), from technological point of view, the most interesting examples currently being the semiconductors GaN [77] and AlN [78]. Recent research in ammonobasic conditions indicates that the binary nitrides are formed via ternary amides functioning as intermediate species [67,79] following the assumed reaction Equation (6 4 ] was proposed as possible intermediate compound [79] and was indeed recently found to crystallize in two modifications in the hot zone of the autoclave [67].…”
Section: Ammonobasic Systemsmentioning
confidence: 99%
“…The samples were obtained by AMMONO method described elsewhere [2]. The AMMONO technique allowed to grow nitride crystals at relatively low temperature and pressure conditions (our crystals were obtained at temperatures not exceeding 5500C and pressures below 5 kbar).…”
Section: Ammono Gan Crystalsmentioning
confidence: 99%